THE EFFECT OF COGNITIVE STIMULATION PROGRAMS ON MEMORY FUNCTION IN THE ELDERLY - Agustanti, Dwi; Purbianto, Purbianto; Yunani, Yunani (Universitas Aisyah Pringsewu, 2026)
ABSTRACT This study examines the effectiveness of cognitive stimulation programs in improving memory function among the elderly, based on concerns regarding increasing cognitive decline in aging populations. It was hypothesized that different types of cognitive stimulation would produce measurable improvements in memory scores. A quasi-experimental pre-post design without a control group was used, involving 90 elderly participants aged ?60 years from three health centers, each receiving puzzle, crossword, or dakon interventions over six sessions. Memory ability was assessed using the Mini Mental State Examination (MMSE). The results showed significant improvement in all groups, with the greatest increase demonstrated by the crossword group (p = 0.000), followed by puzzle (p = 0.002) and dakon (p = 0.000). ANOVA confirmed significant differences in effectiveness between the three stimulation types. These findings indicate that structured cognitive stimulation is a practical and effective non-pharmacological strategy to maintain and enhance memory functions in older adults. The study underscores the importance of integrating cognitive stimulation into community elderly programs to support healthy ageing.